2007
DOI: 10.1093/protein/gzm011
|View full text |Cite
|
Sign up to set email alerts
|

Phage display selection of Affibody molecules with specific binding to the extracellular domain of the epidermal growth factor receptor

Abstract: Affibody molecules specific for the epidermal growth factor receptor (EGFR) have been selected by phage display technology from a combinatorial protein library based on the 58-residue, protein A-derived Z domain. EGFR is overexpressed in various malignancies and is frequently associated with poor patient prognosis, and the information provided by targeting this receptor could facilitate both patient diagnostics and treatment. Three selected Affibody variants were shown to selectively bind to the extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
104
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 53 publications
3
104
0
Order By: Relevance
“…The dimer format of each affibody molecule in the bs affibody protein will most likely give an additional increase in functional affinity (avidity), as demonstrated previously [38,39]. Furthermore, high selectivity of the Z HER2:342 and Z EGFR:1907 affibody molecules to their respective target protein has been shown in previous studies [30,39]. In the present study, binding to HER2 and EGFR was confirmed for the bs affibody protein (Figure 2).…”
Section: Single and Dual Binding Biosensor Analysissupporting
confidence: 86%
See 2 more Smart Citations
“…The dimer format of each affibody molecule in the bs affibody protein will most likely give an additional increase in functional affinity (avidity), as demonstrated previously [38,39]. Furthermore, high selectivity of the Z HER2:342 and Z EGFR:1907 affibody molecules to their respective target protein has been shown in previous studies [30,39]. In the present study, binding to HER2 and EGFR was confirmed for the bs affibody protein (Figure 2).…”
Section: Single and Dual Binding Biosensor Analysissupporting
confidence: 86%
“…The affinities (equilibrium dissociation constant, K D ) of the monomeric affibody molecules were previously determined to be 22 pM for Z HER2:342 [30] and 5.4 nM for Z EGFR:1907 [31]. The dimer format of each affibody molecule in the bs affibody protein will most likely give an additional increase in functional affinity (avidity), as demonstrated previously [38,39]. Furthermore, high selectivity of the Z HER2:342 and Z EGFR:1907 affibody molecules to their respective target protein has been shown in previous studies [30,39].…”
Section: Single and Dual Binding Biosensor Analysismentioning
confidence: 59%
See 1 more Smart Citation
“…In Vivo Cellular and Molecular Imaging (ICMI) Laboratory, Vrije Universiteit Brussel (VUB), Brussels, Belgium; 2 Department of Molecular and Cellular Interactions, Vlaams Interuniversitair Instituut voor Biotechnologie (VIB), Vrije Universiteit Brussel (VUB), Brussels, Belgium; 3 Nuclear Medicine Department, UZ Brussel, Brussels, Belgium; 4 Ablynx N.V., Zwijnaarde, Belgium; 5 Department for Molecular Biomedical Research, Vlaams Interuniversitair Instituut voor Biotechnologie (VIB), Brussels, Belgium; 6 Department of Molecular Biology, Ghent University, Ghent, Belgium; 7 Laboratory of Cellular and Molecular Immunology, Vrije Universiteit Brussel (VUB), Brussels, Belgium…”
mentioning
confidence: 99%
“…As a result, the targeted tumors can be visualized only at several hours or even days after tracer injection (2,3). Radiolabeling of receptor ligands has also been reported (4)(5)(6). Blood clearance of these tracers is rapid, but the tumor uptake is only limited.…”
mentioning
confidence: 99%